Developing human rights jurisprudence : conclusions of Judicial Colloquia and other meetings on the Domestic Application of International Human Rights Norms and on Government under the Law 1988-92 (Commonwealth Secretariat LondonGB, 1992)
Brings together the concluding statements of Judicial Colloquia which have met each year since 1988 to consider the domestic application of international human rights norms.
DC